2015
DOI: 10.4238/2015.july.28.10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of heat shock proteins via transcriptome profiling of tree peony leaf exposed to high temperature

Abstract: ABSTRACT. The tree peony leaf is an important vegetative organ that is sensitive to abiotic stress and particularly to high temperature. This sensitivity affects plant growth and restricts tree peony distribution. However, the transcriptomic information currently available on the peony leaf in public databases is limited. In this study, we sequenced the transcriptomes of peony leaves subjected to high temperature using the Illumina HiSeq TM 2000 platform. We performed de novo assembly of 93,714 unigenes (avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Li et al [31] cloned the full-length cDNA of the HPS70 gene of 'Juan Yehong' and found that it has extremely high amino acid homology with the HPS70 amino acid of the same genus Paeonia lactiflora, proving that PsHPS70 is a peony heat shock protein gene. Zhang et al [29] sequenced the transcriptome of peony leaves under high temperature conditions and identified 24 potential heat shock protein genes (HSF) in peony. Jiang Changhua et al [32] used heat-resistant variety 'Fengdanbai' and heat-labile variety 'Haihuang' as experimental materials, and found that the PseIF5A gene of peony can be expressed after heat shock treatment in 'Fengdanbai', but in 'Fengdanbai' Haihuang' does not express, verifying that the heat tolerance of peony varieties is positively correlated with the expression level, while the heat-labile varieties are weakly expressed or not expressed; studies have shown that the recombinant strain of 'Fengdanbai' gene can respond to high/low temperature stress, high Abiotic stresses such as pH, heavy metals, and high salinity.…”
Section: Peony Response To High Temperature Stress Related Genesmentioning
confidence: 99%
“…Li et al [31] cloned the full-length cDNA of the HPS70 gene of 'Juan Yehong' and found that it has extremely high amino acid homology with the HPS70 amino acid of the same genus Paeonia lactiflora, proving that PsHPS70 is a peony heat shock protein gene. Zhang et al [29] sequenced the transcriptome of peony leaves under high temperature conditions and identified 24 potential heat shock protein genes (HSF) in peony. Jiang Changhua et al [32] used heat-resistant variety 'Fengdanbai' and heat-labile variety 'Haihuang' as experimental materials, and found that the PseIF5A gene of peony can be expressed after heat shock treatment in 'Fengdanbai', but in 'Fengdanbai' Haihuang' does not express, verifying that the heat tolerance of peony varieties is positively correlated with the expression level, while the heat-labile varieties are weakly expressed or not expressed; studies have shown that the recombinant strain of 'Fengdanbai' gene can respond to high/low temperature stress, high Abiotic stresses such as pH, heavy metals, and high salinity.…”
Section: Peony Response To High Temperature Stress Related Genesmentioning
confidence: 99%
“…Despite this, molecular studies of high-temperature stress in tree peony, especially related to heat shock proteins (HSPs), do not exist. Zhang et al (2015e) sequenced the transcriptomes of tree peony 'Juan Ye Hong' leaves subjected to high temperature (35-37 °C), and identified 24 potential HSP genes with complete open-reading frames from transcriptomic sequences. Jiang et al (2015) cloned PseIF5A, a gene induced by heat stress, from P. ostii 'Feng Dan Bai'.…”
Section: Genes Related To Stress Tolerancementioning
confidence: 99%
“…Peony is suitable for cool climate and does not tolerate high temperature. In contrast, the summer in Jiangnan is hot and rainy, so peony growth and cultivation in Jiangnan is more influenced by climate ( Zhang et al., 2015 ; Zhu et al., 2021 ). Summer is a critical period for rapid growth of peony leaves, nutrient accumulation and flower bud differentiation, but the high temperature in summer is the main reason that prevents peony from being widely cultivated in Jiangnan ( Wang et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies on heat tolerance of peony have been reported, mainly focusing on the photosynthetic characteristics and physiological and biochemical changes molecular mechanisms; the effect of exogenous hormone addition on high temperature tolerance of peony. It was found that high temperature stress inhibits the activity of superoxide dismutase, intensifies the production of H 2 O 2 and malondialdehyde, inhibits the activity of PSI and PSII and causes damage to the photosynthetic machinery ( Luo et al., 2011 ; Liu et al., 2012 ; Liu, 2019 ); exogenous abscisic acid and epilactone can improve the high temperature tolerance of peony ( Wu et al., 2018 ; Ren et al., 2018 ); and heat shock proteins and heat tolerance genes were identified and verified ( Zhang et al., 2015 ; Liu et al., 2019 ). Studies on the mechanisms of photosynthesis inhibition by high temperature and on the differences in tolerance to high temperatures in different peony cultivars have been limited so far.…”
Section: Introductionmentioning
confidence: 99%